Gallbladder neuroendocrine carcinoma: A rare entity case report with review of literatures (Indian Journal of Case Reports, 2025)
Neuroendocrine neoplasm (NEN) of the gallbladder (GB) is an extremely rare malignancy, accounting for only 0.2% of all NENs. GB-neuroendocrine carcinomas (NEC) are difficult to differentiate from adenocarcinoma on routine imaging. These tumors do not present with specific symptoms. Histopathological examination is the gold standard for the diagnosis of GB-NEC. They have worse outcomes than GB-adenocarcinoma and have disseminated metastases at the time of diagnosis. We present the case of a 65-year-old woman who presented with a GB mass and abdominal pain. Histopathological and immunohistochemical findings revealed GB-NEC.